Recent advances on blinatumomab for acute lymphoblastic leukemia - Zhao, Juanjuan (Exp Hematol Oncol, 2019)
Although complete remission rate of B cell acute lymphoblastic leukemia (B-ALL) has improved significantly over the past few decades, patients with relapsed/refractory ALL still have dismal outcome. Tyrosine kinase inhibitors, antibody–drug conjugates and chimeric antigen receptor T cell therapy are changing the therapy landscape for B- ALL. Blinatumomab, a bi-specific T cell engager, has been approved for patients with relapsed/refractory and minimal residual disease positive B-ALL. This review summarized data from recent clinical trials of blinatumomab for B-ALL treatment.